Native American Ethology and Animal Protectionist Rhetoric in the Long Enlightenment - Thomas Doran (Humanimalia, 2020)
This article explores how ethnographic writing and travel narratives in the long eighteenth century sometimes revealed and other times concealed the influence of Native American folk zoology on scientific knowledge and practice. I argue that various forms of animal-protectionist rhetoric emerged alongside a developing study of animal behavior in the period 1700–1812 as a result of the complex interaction of Euro-colonial and Native American knowledge systems and ethical practices.